(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2023)
The M4 family of Wave Energy Converters consist of 3 rows of floats, with the front two rows rigidly connected and a hinged connection(s) to the back row. The various possible configurations are commonly identified by the number of floats in each row – hence 1-2-1 has 1 float in front, 2 in the middle, and 1 at the rear. A study by Stansby et al 2017 [1] showed that the 1-2-1 and 1-3-2 variants had the lowest cost of energy of all configurations studied. The 1-3-2 variant has subsequently been extensively studied as it provides greater power per machine. However, the 1-2-1 machine has received less attention. In this paper we report, for the first time, wave basin testing of a 1-2-1 variant. The design is a 1:15 scaled version of a 1-2-1 M4 suitable for deployment in the prevailing short period wind waves in King George Sound, Albany, on the south coast of Western Australia. The tests were carried out in the Model Test Basin at the Australian Maritime College, Tasmania. This basin is 35 m x 12 m and tests were run with a water depth of 0.8 m. For modelling operational conditions, the power take-off was represented by a pneumatic ram; in extreme seas the power take-off was removed. Decay tests, irregular operational seas and irregular extreme seas were tested. All waves were long crested. Sea states tested were taken from the scatter diagram for the deployment site in King George Sound. Body displacements, mooring loads, run-up on the middle floats and forces in the PTO (where installed) were measured. Measured motions and power were compared to a linear model. The level of agreement is compared with previous tests on other variants of M4 in the published literature, including the 1-3-2 variant tested in Carpintero-Moreno et al [2] and the 1-1-1 variant tested in Stansby et al [3]. Compared to some other configurations (such as 1-3-2) the 1-2-1 M4 is more prone to roll. Implications of the test results for deployment in King George Sound are discussed. [1] Stansby, P., Moreno, E.C. and Stallard, T., 2017. Large capacity multi-float configurations for the wave energy converter M4 using a time-domain linear diffraction model. Applied Ocean Research, 68, pp.53-64. [2] Carpintero-Moreno, E. and Stansby, P., 2019. The 6-float wave energy converter M4: Ocean basin tests giving capture width, response and energy yield for several sites. Renewable and Sustainable Energy Reviews, 104, pp.307-318. [3] Stansby, P., Moreno, E.C. and Stallard, T., 2015. Capture width of the three-float multi-mode multi-resonance broadband wave energy line absorber M4 from laboratory studies with irregular waves of different spectral shape and directional spread. Journal of Ocean Engineering and Marine Energy, 1, pp.287-298.